Nanoscience in food and agriculture. - Ranjan, Shivendu; Dasgupta, Nandita (Environmental chemist); Lichtfouse, Eric (Sustainable agriculture reviews, 2016)
Nanomaterials with unique properties are currently dramatically improving agriculture and food production. This book is the second on Nanoscience in Food and Agriculture published within the series Sustainable Agriculture Reviews. The chapters address four major topics of applied nanotechnology: food, health, pollution and agriculture. Intellectual property rights of nanotechnologies in food and agriculture are reviewed in the first chapter by Chowdhury et al. Then Brandelli et al. explain the use of nano-encapsulated materials for food packaging in chapter 2. The safety of future food is addressed by Purkayastha and Manhar who review nanosensors for packaging in chapter 3. To improve the quality of food both for nutrition and health, Rao and Naidu discuss the nanoencapsulation of bioactive compounds in chapter 4. Such use of nutraceuticals is exemplified by Singh et al. who describe food fortification of vitamins and minerals encapsulated in silica in chapter 5. Nanotechnology for pollutant detection and removal is reviewed in chapter 6 by Xing-yan Xue et al. The treatment of cancer and other human illnesses using silver nanoparticles is discussed by Kumar and Smita. in chapter 7. Plant illness is then addressed by Kashyap et al. who present the detection of plant pathogens by nanotechnologies in chapter 8. The ecotoxicology of nanomaterials is addressed by Khan et al. who discuss to the toxicity of nanoparticles in soil, microbes, plants and animals in chapter 9. Nanoparticles for sustainable agroecosystems are then presented by Belal and El-Ramady in the last chapter.